HUBUNGAN PERTUNJUKAN WAYANG RUWATAN TERHADAP PEMAHAMAN PENDIDIKAN SENI BUDAYA PADA ANAK - Tri Wahyoe Widodo (Widya Wacana: Jurnal Ilmiah, 2021)
The wayang “ruwatan” performance in the phenomena of life in Java is not only seen as a social phenomenon, but that humans are starting to become aware of the great power outside their souls that can affect their lives. Likewise, the position of a puppeteer is also seen as a wise person who is able to provide advice to members of the community. History of cultural development, “ruwatan” apart from using “wayang kulit purwa” performances can also be carried out in various ways through religious and educational aspects. The younger generation sees this as something mystical or even unseen, even though in reality it is not so. There are several aspects of the perspective of the “ruwatan“ puppet show which have the meaning of strengthening the morale and character of the youth. This is closely related to the educational growth of adolescents at the junior and senior high school levels regarding their understanding of the relationship between moral values and the character of cultural arts through wayang performances. Keywords: Education, Puppet, Ruwatan ABSTRAK Pertunjukan wayang ruwatan dalam fenomena kehidupan di Jawa, tidak sekedar dipandang sebagai suatu gejala sosial, akan tetapi bahwa manusia mulai sadar mengenai kekuatan besar diluar jiwanya yang dapat mempengaruhi dalam kehidupannya. Begitu juga kedudukan seorang dalang juga dipandang sebagai orang yang bijak yang mampu memberikan nasehat kepada anggota masyarakat Sejarah perkembangan budaya, ruwatan selain menggunakan pertunjukan wayang kulit purwa juga dapat dilakukan melalui berbagai macam melalui aspek agama dan aspek pendidikan. Generasi muda memandang ini sebagai suatu hal yang berbau mistis atau bahkan ghaib, padahal kenyataannya tidak begitu. Ada beberapa aspek pandangan dari pertunjukan wayang ruwatan yang memiliki arti penguatan moral dan karakter pemuda. Hal ini berkaitan erat dengan pertumbuhan pendidikan para remaja di tingkat SMP dan SMA mengenai pemahamannya terhadap hubungan nilai moral dan karakter seni budaya melalui pertunjukan wayang. Kata Kunci : Pendidikan, Ruwatan, Wayang